1997
DOI: 10.1093/oxfordjournals.eurheartj.a015476
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of arrhythmogenic markers in systemic hypertension

Abstract: Objective To evaluate the prognostic value of arrhythmogenic markers in hypertensive patients.Design Two hundred and fourteen hypertensive patients without symptomatic coronary disease, systolic dysfunction, electrolyte disturbances or anti-arrhythmic therapy were included. Recordings were made of 12-lead standard ECGs with calculations of QT interval dispersion, 24 h Holter ECGs (204 patients), echocardiography (187 patients) and signal-averaged ECGs (125 patients).Results Baseline data: echocardiographic lef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 28 publications
2
19
0
1
Order By: Relevance
“…Galinier et al (Galinier et al, 1992) and Franchi et al (Franchi et al, 1992) found a greater prevalence of LVPs in subjects with eccentric LVH than in those with concentric hypertrophy. Nonsustained VT has been found to have a prognostic value in HT patients (Galinier et al, 1997). Vardas et al (Vardas et al, 1994) and Palatini et al (Palatini et al, 1995) confirmed that a high prevalence of ventricular arrhythmias was associated with LVPs in HT patients.…”
Section: Hypertension (Ht)mentioning
confidence: 94%
See 1 more Smart Citation
“…Galinier et al (Galinier et al, 1992) and Franchi et al (Franchi et al, 1992) found a greater prevalence of LVPs in subjects with eccentric LVH than in those with concentric hypertrophy. Nonsustained VT has been found to have a prognostic value in HT patients (Galinier et al, 1997). Vardas et al (Vardas et al, 1994) and Palatini et al (Palatini et al, 1995) confirmed that a high prevalence of ventricular arrhythmias was associated with LVPs in HT patients.…”
Section: Hypertension (Ht)mentioning
confidence: 94%
“…The risk of SCD due to ventricular arrhythmias was demonstrated by a prolonged QT interval or LVPs. The most important mechanisms by which HT predisposes to SCD are: the degree of left ventricular hypertrophy (LVH), interstitial fibrosis, myocardial or subendocardial scars, silent myocardial ischemia, diastolic dysfunction and disturbances in cardiac autonomic balance (Galinier et al, 1997;Kaftan AH & Kaftan O, 2000;Palatini et al, 1995;Yildirir et al, 2002). Coronary artery disease may interact with LVH in the genesis of ventricular arrhythmias and SCD (Galinier et al, 1997).…”
Section: Hypertension (Ht)mentioning
confidence: 99%
“…Marked left ventricular hypertrophy (LVH) is associated with potentially arrhythmogenic ventricular repolarization abnormalities and may generate conditions for QT interval (QTi) prolongation and increase QT dispersion (QTd)) [15,16]. Prolongation of QTc interval and QTd are risk markers for malignant ventricular arrhythmias (VA) and sudden cardiac death [17,18].…”
Section: Qt Interval and Qt Dispersionmentioning
confidence: 99%
“…Such a patient cohort is difficult to investigate by noninvasive testing. 15,16 The invasive electrophysiological study can help to reproduce sustained ventricular tachyarrhythmias in a certain percentage of patients with prior documented ventricular tachycardia/ ventricular fibrillation, but the prognostic accuracy in hypertensive patients is weak. 17 In this entity of heart muscle disease the analysis of TWA may be a new parameter for risk stratification.…”
Section: Hennersdorf Et Al T Wave Alternans In Hypertension 201mentioning
confidence: 99%